(untitled) (Economic studies journal, 2024)
The aim of this research is to measure the impact of Organizational Virtuousness on enhancing organizational reputation and analyzing the relationship between Organizational Virtuousness and organizational reputation through organizational pride as an intermediate variable in the Damietta and Port Said port authorities and using the descriptive analytical approach, and collecting theoretical information from library sources, and data through a questionnaire distributed to (342) individual employees of the Damietta and Port Said port authorities, the number of valid ones for statistical analysis (256) single has been using the statistical package for social sciences (SPSS V.26) and the program (AMOS V.26) To analyze the data and test the hypotheses of the study, the study has reached several results, the most important of which is the existence of a statistically significant impact of Organizational Virtuousness in its various dimensions and between organizational reputation, as well as that the entry of organizational pride in the relationship between Organizational Virtuousness and organizational reputation led to an increase in the impact of organizational integrity The study recommended a set of recommendations The need to increase the support of senior management in ports Focus on creating a set of innovative logistics services capable of transferring the level of services within ports to an advanced level, and setting standards And frameworks and rules, with an emphasis on their application, which determine the mechanisms and criteria for selecting administrative leaders, and provide a set of training programs and workshops that help workers increase their skills and identify modern methods and means of work.